1986
DOI: 10.5006/1.3584889
|View full text |Cite
|
Sign up to set email alerts
|

Galvanic Corrosion Prediction Using Long- and Short-Term Polarization Curves

Abstract: Long-term potentiostatic polarization curves of up to 120 days duration were developed for the following materials in seawater: 90:30 copper:nickel (C70600), Monel 400 (N04400), Inconel 625 (N06625), Navy M-bronze (C92200), nickel-aluminum bronze (C95800), HY-80 steel, titanium 50 (R50400), 70:30 copper:nickel (C71500) and anode grade zinc (MIL-STD 18001). In addition, shcrt-term potentiodynamic polarization curves were developed at four scan rates and two pre-exposure levels for all materials. The scan rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The four repeated measurements showed reasonable agreement. Hack and Scully [57] indicated that it was necessary to use long-term po- larization curves to adequately predict the galvanic corrosion, and as a consequence, galvanostatic curves were measured. The particular current density values, chosen based on the potentiostatic polarization curves, were applied and the resulting potential was measured as shown by typical curves in figure 8.…”
Section: Polarization Curvesmentioning
confidence: 99%
“…The four repeated measurements showed reasonable agreement. Hack and Scully [57] indicated that it was necessary to use long-term po- larization curves to adequately predict the galvanic corrosion, and as a consequence, galvanostatic curves were measured. The particular current density values, chosen based on the potentiostatic polarization curves, were applied and the resulting potential was measured as shown by typical curves in figure 8.…”
Section: Polarization Curvesmentioning
confidence: 99%
“…Variation in n-a-b polarization response based on the experimental procedure used to obtain this material behavior characteristic have been observed [12]. Variation in physical scale modeling and computational results could be indicative of the intrinstic variation in the polarizaton response.…”
Section: Comparison Of Resultsmentioning
confidence: 95%
“…as well as the material polarization response used in the computational model. Material polarization response curves have been observed to vary based on the experimetal technique used and even to vary with the SCan rate used [12] so variation between computational and experimental results of the order observed is possible. It is also important to thoroughly understand the effects of even what may at first seem minor geometric details.…”
Section: Discussionmentioning
confidence: 99%
“…Hack and Scully [40] indicated that it was necessary to use long-term polarization curves to adequately predict the galvanic corrosion, and as a consequence, galvanostatic curves were measured. The particular current density values, chosen based on the potentiostatic polarization curves, were applied Potentiodynamic polarization curves for AZ91D and steel in 5% NaCl solution using a scan rate of 2 mV/s.…”
Section: Polarization Curvesmentioning
confidence: 99%